Association of the ATP-Binding Cassette Transporter A1 R230C Variant With Early-Onset Type 2 Diabetes in a Mexican Population - Villarreal-Molina, M. Teresa; Flores-Dorantes, M. Teresa; Arellano-Campos, Olimpia; Villalobos-Comparan, Marisela; Rodríguez-Cruz, Maricela; Miliar-García, Angel; Huertas-Vazquez, Adriana; Menjivar, Marta; Romero-Hidalgo, Sandra; Wacher, Niels H.; Tusie-Luna, M. Teresa; Cruz, Miguel; et al. (Diabetes (New York, N.Y.), 2008)
Association of the ATP-Binding Cassette Transporter A1 R230C Variant With Early-Onset Type 2 Diabetes in a Mexican Population M. Teresa Villarreal-Molina 1 , M. Teresa Flores-Dorantes 1 , Olimpia Arellano-Campos 2 , Marisela Villalobos-Comparan 1 , Maricela Rodríguez-Cruz 3 , Angel Miliar-García 4 , Adriana Huertas-Vazquez 1 , Marta Menjivar 5 , Sandra Romero-Hidalgo 6 , Niels H. Wacher 7 , M. Teresa Tusie-Luna 1 , Miguel Cruz 7 , Carlos A. Aguilar-Salinas 2 , Samuel Canizales-Quinteros 1 and the Metabolic Study Group 1 Unit of Molecular Biology and Genomic Medicine, Salvador Zubiran National Institute of Medical Sciences and Nutrition (INCMNSZ), Institute of Biomedical Research, National Autonomous University of Mexico, Mexico City, Mexico 2 Department of Endocrinology and Metabolism, INCMNSZ, Mexico City, Mexico 3 Unit of Medical Research in Nutrition, Pediatrics Hospital, National Medical Center XXI Century, Mexican Institute of Social Security, Mexico City, Mexic 4 Postgraduate Studies and Research Section, Postgraduate Studies and Research Section, School of Medicine, National Polytechnic Institute, Mexico City, Mexico 5 Department of Biology, Faculty of Chemistry, National Autonomous University of Mexico, Mexico City, Mexico 6 National Coordination of Genetic Medicine, Institute of Social Security and Services for Government Employees, Mexico City, Mexico 7 Units of Medical Research in Clinical Epidemiology and Biochemistry, Specialties Hospital, National Medical Center XXI Century, Mexican Institute of Social Security, Mexico City, Mexico Address correspondence and reprint requests to Samuel Canizales-Quinteros, PhD, Unidad de Biología Molecular y Medicina Genómica, Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán, Vasco de Quiroga #15 Colonia Sección 16, Tlalpan 14000, México D.F. E-mail: caniatservidor.unam.mx Abstract OBJECTIVE— The ATP-binding cassette transporter A1 (ABCA1) R230C variant is associated with low HDL cholesterol levels, obesity, and the metabolic syndrome in Mexican-Mestizos. Because a pivotal role for ABCA1 in pancreatic β-cell function was recently observed in the mouse model, we assessed the association of this variant with type 2 diabetes in this population. RESEARCH DESIGN AND METHODS— The initial group included 446 unrelated Mexican individuals: 244 with type 2 diabetes aged 20–69 years (121 with onset ≤45 years), and 202 nondiabetic control subjects aged >50 years. An independent study group included 242 type 2 diabetic case subjects and 225 control subjects with similar characteristics. RESULTS— R230C/C230C genotypes were significantly more frequent in type 2 diabetic individuals (24.6%) than in control subjects (11.4%) in the initial study group (OR 2.501; P = 0.001). After stratifying by age at diagnosis, the association was significant only in the early-onset group (age at diagnosis ≤45 years) (OR 3.776, P = 3.3 × 10 −6 ). Both associations remained significant after adjusting for admixture ( P = 0.0008 and P = 8.1 × 10 −6 , respectively). Similar trends were observed in the independent study group, and the combined analysis of both populations showed a highly significant association of the R230C variant with type 2 diabetes, particularly with that of early onset ( P = 7.6 × 10 −6 and 9.4 × 10 −8 , respectively). CONCLUSIONS— The R230C ABCA1 variant is associated with type 2 diabetes, particularly of early onset, in the Mexican-Mestizo population. ABCA1, ATP-binding cassette transporter A1 AIM, ancestry informative marker Apo A-I, apolipoprotein A-I LD, linkage disequilibrium SNP, single nucleotide polymorphism Footnotes M.T.V.-M. is currently affiliated with the National Institute of Genomic Medicine. Published ahead of print at http://diabetes.diabetesjournals.org on 14 November 2007. DOI: 10.2337/db07-0484. Additional information for this article can be found in an online appendix at http://dx.doi.org/10.2337/db07-0484 . M.T.V.-M. and M.T.F.-D. contributed equally to this work. A complete list of individuals and institutions participating in the Metabolic Study Group appears in the appendix . Accepted November 7, 2007. Received April 6, 2007. DIABETES